Agriculture 4.0 – an opportunity or threat to Polish agriculture - Niewiadomska, Agata (Przegląd Prawa Rolnego, 2024)
The purpose of the article is to assess the state of Polish agricultural law in the implementation of legal and financial mechanisms of Agriculture 4.0. Agriculture 4.0 is a modern concept assuming an approach to agriculture expected to increase efficiency and to balance agricultural production through the use of technology. The technologies currently in use monitor and manage the cultivation processes primarily with the help of remote control of the machinery, using GPS, or robots. As most analyses show, Agriculture 4.0 has become a challenge for new legal solutions and their clear formulation directed at the provision of maximum assistance to farmers. At the same time, there are also risks that without public aid, farmers might be unable to acquire expensive solutions for running their businesses. The adopted research hypotheses also assume an assessment of the state of Polish and European agricultural law in the perspective of technical progress in agriculture in countries outside the EU. The article also emphasises the lack of uniformity of legal instruments designed to assist farmers wishing to take advantage of aid mechanisms available under Agriculture 4.0.